(untitled) (PANGEEA, 2025)
Noise pollution represents a topical and common issue, especially in agglomerations and it is caused mainly by road traffic, rail traffic, industrial and commercial activities, but it can be generated also by other human activities, which, cumulated, represent the environmental noise that may induce harmful effects on human health and welfare. Road traffic is considered to be the main source of noise pollution, due to the steady growth of the number of vehicles that pass the public roads, correlated, in some areas, with the poorly developed infrastructure. The number of persons exposed to noise exceeding the limit values is constantly increasing, although in many countries there are already in force noise-reduction measures. Prolonged exposure to high level noise may cause a series of health problems, such as: sleep disturbance, mental problems, hear loss, cardiovascular diseases, stress etc. The level of exposure to road traffic noise depends on a series of factors, among which the most important are: the type of road, the traffic intensity, the noise reduction measures, the type of building, the characteristics of the vehicles and the behavior of drivers. The reduction of road traffic noise ranks high on the authorities’ agenda worldwide. This issue is common in many agglomerations from Romania too, because of the increased number of vehicles, the low renewal rate of cars and the poorly developed infrastructure, which is not able to respond to increasing traffic. This study aimed to identify the noise level in different areas of Aiud city, Alba county, located nearby National Road 1, which crosses the city.